Role of Youth in Strengthening Parliamentary Federal Democracy in Nepal - Prasai, Khagendra (Molung Educational Frontier, 2018)
Politics has become a frustrating social activity for many young people. However, there is no escape from it: the only choice in democratic society is between ―good‖ politics and ―bad‖ politics. The performance of ―independent‖ media, our cultural and social norms, some constitutionals provisions, liberalism and cynicism are among those principal factors that are responsible for the alienation of you from politics. Federal structure, in the meantime, has encouraged the youth to engage in politics. In a federal-democratic society, youth needs to possess critical and deliberative mind to make politics meaningful and productive. This paper explores the roles youth can play in strengthening federal democracy in Nepal.